2019
DOI: 10.21521/mw.6240
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous screening of antibiotic residues in honey by biochip multi-array technology

Abstract: The existence of antibiotic residues in food causes serious health problems in humans. This study aims to determine antibiotic residues in honey intended for consumption. Evidence Investigator™ Biochip Array technology enables simultaneous quantitative detection of multiple analytes on a single sample. The Anti Microbial Array IV test kit is used in simultaneously detecting the quantity of 12 different groups of antimicrobials in honey samples. A competitive chemiluminescent immunoassay was employed for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The validated method allows fast screening of nitrofuran residues from a single sample compared with other methodologies with LODs below 1 ppb. The same method was evaluated and applied to the screening of honey samples of different geographic regions and was found suitable as a screening tool for detecting nitrofuran metabolites (8,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The validated method allows fast screening of nitrofuran residues from a single sample compared with other methodologies with LODs below 1 ppb. The same method was evaluated and applied to the screening of honey samples of different geographic regions and was found suitable as a screening tool for detecting nitrofuran metabolites (8,23).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence investigator analyzer is a semi-automated benchtop device. The system has clinical, forensic, and veterinary applications (3,7,8). To our knowledge, there are limited publications on detecting four nitrofuran metabolites in honey with this system (9).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that residues of erythromycin, streptomycin, neomycin, tylosin B, amikacin and lincomycin were found in honey samples at different concentrations. Among them, erythromycin can be detected in 91% of local honey samples [48].…”
Section: Molecular Biological Techniquementioning
confidence: 99%
“…AKSEM AKSOY performed the experiment regarding screen and evaluated the presence of possible 12 different antibiotic residue simultaneously in honey based on biochip multi-array technology. Regarding to the detection analyses, the results showed that streptomycin, erythromycin, tylosin B, neomycin, lincomycin, and amikacin residues were observed in honey samples in numerous concentrations (Aksoy, 2019). Another study has been conducted by Mi-Sun Ha and for the detection of enrofloxacin by using biochips and microparticles.…”
Section: Other Immunoassaymentioning
confidence: 99%